Combination therapy with ezetimibe and simvastatin to achieve aggressive LDL reduction. (July 2006) - Robinson, Jennifer G; Davidson, Michael H
A low-density lipoprotein (LDL) cholesterol goal of less than 100 mg/dl is recommended for patients at moderate to high risk of cardiovascular disease with an optional LDL goal of less than 70 mg/dl for patients at a very high risk of cardiovascular disease. Most patients will require reductions in LDL of more than 50% in order to achieve these more aggressive goals. Only a few agents will lower LDL by at least 50%. This review will focus on the efficacy and safety ezetimibe/simvastatin coadministered as a therapy with enhanced LDL-lowering efficacy, while minimizing the adverse effects of statins in a wide range of patients. Ezetimibe 10 mg/simvastatin 80 mg lowers LDL by approximately 60% and has been demonstrated to be superior to the highest doses of atorvastatin and rosuvastatin for lowering LDL and raising high-density lipoprotein.